Biomechanical analysis of the shot put at the 12th IAAF World Indoor Championships - Gutierrez-Davila, M.; Rojas, J.; Campos, J.; Gamez, J.; Encarnacion, A. (New Studies in Athletics, 2009)
The variability expressed in the descriptive research about the shot put indicates the existence of successful individual techniques that do not correspond to any common ideal pattern. The aim of this study was to make a descriptive analysis of the techniques of the finalists in the 12th IAAF Indoor World Championships. To do this, three-dimensional photogrammetric techniques were used and the action was recorded with two video cameras temporally synchronized at 100Hz. Six puts were recorded for each of the men's and women's finalists and the longest put of each thrower was studied. A temporal analysis of the put was made and the throwing action was divided into six phases. Starting from these phases, graphs of the tangential velocity of the thrower's CM and the time taken are described. Then the factors that determine the trajectory of the shot during flight (product factors) and the contribution of the other causal factors to the put were measured. As well as confirming the relation between the product factors, the results show that each thrower uses his/her own temporal sequence and rhythm of execution, confirming that the technical execution is individual and conditioned by antropometrical characteristics, muscular capacity and the degree of automation of individual temporal sequence.